2019
DOI: 10.21203/rs.2.13503/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolution of comorbidities in people living with HIV between 2004 and 2014: Cross-sectional analyses from ANRS CO3 Aquitaine Cohort

Abstract: Objective The objective of the present study was to describe the evolution of chronic non-AIDS related diseases and their risk factors, in patients living with HIV (PLHIV) included in the French ANRS CO3 Aquitaine prospective cohort, observed both in 2004 and in 2014 in order to improve long-term healthcare management. Patients and Methods The ANRS CO3 Aquitaine cohort prospectively collects epidemiological, clinical, biological and therapeutic data on PLHIV in the French Aquitaine region. Two cross sectional … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Several lines of evidence have suggested that PLWH use corticosteroids at a higher rate than the general population, due to their comorbidities and autoimmune disorders. 13,24,25 It has been shown that clinicians avoid prescribing corticosteroids to PLWH out of concern for adverse outcomes. 26 Drug-drug interactions between HAART and corticosteroids or other medications can explain the increased risk of severe infections in PLWH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several lines of evidence have suggested that PLWH use corticosteroids at a higher rate than the general population, due to their comorbidities and autoimmune disorders. 13,24,25 It has been shown that clinicians avoid prescribing corticosteroids to PLWH out of concern for adverse outcomes. 26 Drug-drug interactions between HAART and corticosteroids or other medications can explain the increased risk of severe infections in PLWH.…”
Section: Discussionmentioning
confidence: 99%
“…9,31 A literature review of cases reports on systemic erythematous lupus (SLE) and HIV included 55 PLWH with SLE. The median age was 32 years old [23][24][25][26][27][28][29] and median CD4 count of 353/mm 3 [214-560.] Fifty-three patients received treatment for SLE of which 52.2% were administered corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Although NCD and multimorbidity accumulate with older age among PWH [12,15], this doesn't appear to be a legacy effect from pre-ART era AIDS related disease as risk is not associated with the calendar period of HIV diagnosis [12]. Indeed, NCDs may be accruing early in life as the differences compared to HIV negative individuals are more pronounced in younger PWH; in the WHIS cohort, women <25 years old had the greatest NCD incidence rate ratio [7] and in the UK hazard ratios for hypertension (HTN), chronic kidney disease (CKD) and ischaemic heart disease (IHD) are higher in PWH under, rather than over, 40 years old [9].…”
Section: Burden Of Multimorbiditymentioning
confidence: 99%
“…However, HIV specialists have found themselves widening their scope of care provision, while the HIV focused model has rarely changed. For example, a recent cross-sectional analysis from France found a significant increase in use of NCD preventive medication (statins, clopidogrel, aspirin) in PWH [15]. The potential deficiency of the single disease model of HIV care was strikingly illustrated by a 20-year analysis of the Multicentre AIDS Cohort Study cohort that found risk for incident DM in men with prediabetes was 40% (95% confidence interval [CI]: 0–80%) higher among PWH after adjusting for competing risk factors [20].…”
Section: Burden Of Multimorbiditymentioning
confidence: 99%